Wheat rust early warning works for Ethiopian farmers - CGIAR Research Program on Wheat (2021)
In Ethiopia, almost 5 million smallholder farmers grow wheat and struggle with virulent, rapidly-evolving strains of stem and yellow rust. Working with national and international partners in Ethiopia and funded by bilateral donors, WHEAT scientists collaborated to fight rust through surveillance, advanced epidemiological modelling and an alert system for farmers.